2022
DOI: 10.1021/acs.jmedchem.2c00654
|View full text |Cite
|
Sign up to set email alerts
|

Selective C9orf72 G-Quadruplex-Binding Small Molecules Ameliorate Pathological Signatures of ALS/FTD Models

Abstract: The G-quadruplex (G4) forming C9orf72 GGGGCC (G4C2) expanded hexanucleotide repeat (EHR) is the predominant genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Developing selective G4-binding ligands is challenging due to the conformational polymorphism and similarity of G4 structures. We identified three first-in-class marine natural products, chrexanthomycin A (cA), chrexanthomycin B (cB), and chrexanthomycin C (cC), with remarkable bioactivities. Thereinto, cA shows the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Furthermore, we demonstrated how the G4-ligand PDS can diminish mG4-induced aggregation of (GGGGCC) 10 by driving the system to a lower molecularity state. In previously reported studies, G4-ligands have been shown to prevent aggregation events in ALS/FTD phenotypes 26,24 . It was hypothesised that the ligands interfere with the downstream biological functions of the gene, specifically in relationship to the toxic translated protein 52 , or displace proteins bound to the repeats.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, we demonstrated how the G4-ligand PDS can diminish mG4-induced aggregation of (GGGGCC) 10 by driving the system to a lower molecularity state. In previously reported studies, G4-ligands have been shown to prevent aggregation events in ALS/FTD phenotypes 26,24 . It was hypothesised that the ligands interfere with the downstream biological functions of the gene, specifically in relationship to the toxic translated protein 52 , or displace proteins bound to the repeats.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, the candidacy of these structures as potential therapeutic targets is demonstrated by using small-molecule probes that bind to and stabilise their secondary structures, leading to amelioration of disease phenotypes 20,21,22,23,24,25 . In particular, the use of ligands to bind G4s has been shown to ameliorate ALS phenotypes in neuronal cells 20,24,26,27 and targeting of the hairpin with a small molecule inhibited repeat-associated non-ATG (RAN) translation and subsequent generation of toxic dipeptide repeats from the C9orf72 gene mutation 21 . However, none of these studies have fully clarified the role of the nucleic acid structures in the regulation of pathological aggregation, which is a pre-requisite to devising optimised therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligands that bind to G-quadruplexes or triplex structures are known. Ligands specific to the structures formed by disease-specific DNA and RNA repeat motifs have been shown to inhibit gene expression, alter gene splicing, or alter repeat instability ( 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ). Understanding the disease-specific DNA and RNA structures formed by the CANVAS-causing repeat motifs in RFC1 , relative to the nonpathogenic motifs, is a beginning to opening such therapeutic paths.…”
Section: Discussionmentioning
confidence: 99%
“…A wide-spectrum GQ ligand, TMPyP4, was reported to be able to mitigate neurotoxicity in Drosophila models by altering the structure of C9-HRE RNA GQ, which causes an inhibition of the toxic repeat-associated non-AUG (RAN) translation [ 30 , 31 , 32 ]. Zhu [ 33 ] and other groups [ 34 , 35 ] have reported that small-molecule ligands targeting C9-HRE RNA GQ can significantly reduce RNA foci and DPRs levels, and thus ameliorate C9ALS/FTD pathology in vitro and in vivo. Although the pathological efficacy of small-molecule ligands targeting C9-HRE DNA GQs still needs to be addressed, it is posited that modulating the stability or topology of C9-HRE DNA GQ structures might contribute to the impediment of transcription within the C9-HRE locus, and thus reduce the overall C9-HRE-linked gain-of-function pathogenic mechanisms, such as ribonucleoprotein sequestration by RNA foci or the RAN translation of toxic DPRs [ 36 ].…”
Section: Introductionmentioning
confidence: 99%